1996
DOI: 10.1021/jf950751y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of Novel Bis(dithiocarbamate) Derivatives of Glycerol

Abstract: Three bis(dithiocarbamate) derivatives of glycerol were obtained in 30−95% yields by reaction of a dithiocarbamic acid salt with 1,3-dichloro-1,3-dideoxyglycerol. The in vitro antifungal activity of the new compounds was evaluated against Alternaria brassicae, Pseudocercosporella herpotrichoides, Septoria nodorum, and Phytophtora cinnamomi. Some of the compounds displayed greater activity than commercial fungicides. Bis(N,N-diethyldithiocarbamoyl)-1,3-dideoxyglycerol (4) was found to maintain its pesticidal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 7 publications
1
52
0
1
Order By: Relevance
“…The residue was chromatographed on silica gel (EtOAc/CH 3 4-Methylpiperazine-1-carbodithioic acid 3-(5-tetrazolyl)-3,3-diphenylpropyl ester (18) A mixture of the lead compound 1 (792 mg, 2.0 mmol), sodium azide (390 mg, 6.0 mmol) and triethylamine hydrochloride (828 mg, 6.0 mmol) in toluene (10 mL) was refluxed for 48 h. After cooling, the product was extracted with water (2 Â 10 mL). The aqueous layer was neutralized to pH 7 with 5% HCl solution, and then extracted with ethyl acetate (4 Â 10 mL).…”
Section: -(4-methylpiperazin-1-yl)-22-diphenylbutanenitrile (12c)mentioning
confidence: 99%
See 1 more Smart Citation
“…The residue was chromatographed on silica gel (EtOAc/CH 3 4-Methylpiperazine-1-carbodithioic acid 3-(5-tetrazolyl)-3,3-diphenylpropyl ester (18) A mixture of the lead compound 1 (792 mg, 2.0 mmol), sodium azide (390 mg, 6.0 mmol) and triethylamine hydrochloride (828 mg, 6.0 mmol) in toluene (10 mL) was refluxed for 48 h. After cooling, the product was extracted with water (2 Â 10 mL). The aqueous layer was neutralized to pH 7 with 5% HCl solution, and then extracted with ethyl acetate (4 Â 10 mL).…”
Section: -(4-methylpiperazin-1-yl)-22-diphenylbutanenitrile (12c)mentioning
confidence: 99%
“…Dithiocarbamic acid esters, a common class of organic molecules exhibit a variety of valuable biological effects, including antibacterial activity [1,2], antifungal activity [3], the ability to chelate heavy metals [4,5], and to function as NO scavengers [6]. Moreover, it was recently found that some kind of dithiocarbamic acid esters have cancer chemopreventive and anticancer action, which have received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that especially sulfur-containing derivatives exhibited promising antiproliferative efficiency towards several tumor cell lines [19,20]. Dithiocarbamates have been attracting considerable interest because of their diverse activities [21][22][23][24] and in the treatment of cancer [25,26]. Our group recently reported the synthesis of a novel thalidomide-containing dithiocarbamate moiety; several derivatives exhibited potent anti-cancer activity [27,28].…”
Section: Introductionmentioning
confidence: 98%
“…An enormous quantity of glycerol is being produced by the oleochemical and biodiesel industry and is used as a base chemical for the production of value added products [1][2][3][4][5][6][7][8][9][10][11][12][13]. It has enormous applications in the food industry, pharmaceutical and personal care preparations.…”
Section: Introductionmentioning
confidence: 99%